PHARMACOKINETIC COMPARISON OF MONTELUKAST SODIUM FORMULATIONS AFTER A SINGLE ORAL DOSE IN HEALTHY GUINEA PIGS - SINGH, NEELAM; Kulkarni, Giriraj T; Kumar, Yatendra; T KULKARNI, GIRIRAJ (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Pharmacokinetic evaluation of montelukast sodium chronomodulated capsules (sustained-release solid dispersion of drug enclosed in pH-sensitive film-coated hard gelatin shell) and marketed tablets has been carried out in this study. Methods: A single oral dose of prepared capsules and marketed conventional tablets was administered in healthy male Dunkin-Hartley albino guinea pigs. Blood samples were collected at different time intervals and plasma concentration of drug was determined by reversed-phase high-performance liquid chromatography. Different pharmacokinetic parameters were assessed from plasma drug concentration-time profile by one-compartment model, first-order kinetics. Results: Pharmacokinetic parameters such as time to reach maximum concentration, elimination rate constant, elimination half-life, and mean residence time data indicates that drug release from chronomodulated capsules is significantly prolonged with initial release lag time of 3.5–4 h in comparison with marketed conventional tablets. However, maximum drug plasma concentration, area under the concentration-time curve, and apparent volume of distribution values show non-significant difference between capsules and marketed tablets. Conclusion: The findings specified that capsules were providing time controlled delivery of drug at a desired rate for prolonged time, which may be helpful for the prevention of episodic attack of asthma in early morning hours.